(untitled) (Fiep Bulletin - online, 2011)
When searching on education in prison, within the prisons, we note that the methodology is the distinguishing factor of educational work, it allows the engagement of education to prison management procedures, guided by the principle of punishment and the maintenance of internal order in prisons. Based on the understanding that education is a fundamental right of human, this article begins with a discussion of education for human rights, walking slowly to the study of reality in the women’s capital penitentiary. The goal is to recognize the school’s role in building awareness of Citizenship and the preservation of human rights. The school not only can play a key role in building and developing a social consciousness, especially the education of the prison, where its members have lost half their human rights. Education for human rights is an education on human rights and has to bridge the gap often between knowledge and action. Content to mention the human rights and require memorization is not suitable for an education that aims to attitudes of respect for others and actions to promote awareness about the rights. The conventional school system applied in prisons is a total failure, as a transforming agent of the inmate population, because only dare to instruct and train for material things, which is very little in the way of transformation. We must educate prisoners, emphasizing moral principles, ethical, guiding their lives, directing them to the spirit of mutual cooperation, rather egocentric competition imposed on them by the mainstream and formal.